Terrorist Attacks, Managerial Sentiment, and Corporate Disclosures - Chen, Wen; Wu, Haibin; Zhang, Liandong (The Accounting Review, 2021)
This study investigates the effect of managerial sentiment on corporate disclosure decisions. Using terrorist attacks in the United States as adverse shocks to managerial sentiment, we find that firms located in the metropolitan areas attacked issue more negatively biased earnings forecasts. The effect is stronger for firms with higher operating uncertainty and firms with younger, inexperienced, or less confident executives and it is weaker for firms located in states with increasing violent crime rates. A potential alternative explanation is that managers strategically bias earnings forecasts downward and attribute the poor performance to terrorist attacks. To address this issue, we conduct a battery of additional analyses and find results more consistent with managerial sentiment than strategic attribution. In addition, we show that our results are unlikely to be driven by any economic effects of terrorist attacks. Finally, firms in attacked areas exhibit a more pessimistic tone in 10-K/10-Q filings.